Optimization of visibility and quantification of aberrant crypt foci in colonic mucosa in Wistar rats - Burlamaqui,Idália Maria Brasil (2010)
PURPOSE: Test immersion of microscopy samples in water as an aid to visualizing and quantifying aberrant crypt foci (ACF) in rat colon mucosa. METHODS: Carcinogenesis was induced with azoxymethane in Wistar rats kept on a conventional diet or a hypercaloric diet containing unsaturated fat. Fifteen weeks after induction, colon samples were retrieved and fixated in a 10% formaldehyde solution. The samples were divided into segments (distal, middle, proximal) and stained with 1% toluidine blue. The technique tested in the study consisted of immersing microscopy samples in distilled water in order to eliminate the problem of light reflection known from conventional microscopy. RESULTS: When samples were immersed in water during microscopy, significantly more ACF could be visualized in all colon segments than with the conventional method proposed by Bird. CONCLUSION: Immersing microscopy samples in water aids the visualization and quantification of aberrant crypt foci in rat colon mucosa fixed in formaldehyde.